The Effect Of Smash Drill Training Behind The Offensive Line On The Success Of Volleyball Smash Back Attack In SMAN 1 Ciwaru - Citra, Citra Dwi Tahara; Fauzan, Elang (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
The effect of drill smash drill training behind the attack line on the success of volleyball smash back attack in extracurricular students of SMAN 1 Ciwaru. Health and Recreation Physical Education Study Program. Drill smash drill practice behind the attack line against the success of smash back attack through the goal jumping method, performing vertical jump movements continuously in 16 meetings, which aims to improve smash back attack in volleyball game, smash Included in the basic technique of volleyball games that aim to attack or otherwise win points with great opportunities, the series of smash movements are: Start, Reject, Attack, Landing and the series must be done properly and correctly. This research is an experimental research. The population in this study is 25 people and the sample in this study is 15 people. The sampling technique used is purvosive sampling where the author determines the sample in a smash position in a volleyball game. The data collection technique is with pretest and posttest where the sample must smash for 8 times, and the target of the ball falling on the field that has been given a number is calculated. Based on statistical calculations, obtained from the results of the t-test of 0.000 or it can be interpreted that there is an influence in the drill smash drill exercise behind the attack line on the success of smash back attack in extracurricular students of SMAN 1 Ciwaru.